Double responsibility of foreign language teachers: Primary student-teachers’ perceptions of linguistic and cultural content - Sanchez-Sanchez, Gabriel; Krawiec, Marek; Ibañez-Lopez, Francisco Javier (Glottodidactica, 2020)
Scholars all over the world have been arguing for foreign language instruction which combines linguistic and cultural content. Eliminating the cultural side results in a deficient process. This study explored prospective teachers’ perceptions of both constituents, since they will ultimately be responsible for their implementation in the foreign language classroom. To this end, 137 students from three European universities were chosen and asked to fill out an online questionnaire with Likert scale items. Data was collected and interpreted using the free statistics software package R (R Core Team, 2019). The findings confirmed that the relevance of linguistic / cultural issues was unanimously acknowledged (98,5%), speaking was appointed as the most desired target skill (97,1%), interpersonal relations (88,3%) as the most important aspect of socio-cultural knowledge, and lessons with native speakers (94,2%) as the most relevant classroom resource.